A revision of Hoodia and Lavrania (Asclepiadaceae-Stapelieae) - Bruyns, Peter V (Department of Biological Sciences, 2016)
Hoodia Sweet ex Decne is revised to contain 13 species which are divided into 2 sections. Sect. Hoodia contains H.currorii, H.dregei, H.gordonii, H.juttae and H.parviflora. Sect. Trichocaulon contains H.alstonii, H.flava, H.mossamedensis, H.officinalis, H.pedicellata, H.pilifera, H.ruschii and H.triebneri, all except H.ruschii formerly constituting the section "Eutrichocaulon", the so-called "spiny" species of Trichocaulon. The remainder of Trichocaulon, the section Cactoidea, is transferred to Lavrania Plowes. This genus then consists of the monotypic section Lavrania (L.haagnerae) and Sect. Cactoidea containing L.cactiformis, L.marlothii, L.perlata and L.picta.